2015
DOI: 10.1038/modpathol.2015.91
|View full text |Cite
|
Sign up to set email alerts
|

GNAS mutations are not detected in parosteal and low-grade central osteosarcomas

Abstract: Parosteal osteosarcoma, low-grade central osteosarcoma, and fibrous dysplasia share similar histological features that may pose a diagnostic challenge. The detection of GNAS mutations in primary bone tumors has been useful in clinical practice for diagnosing fibrous dysplasia. However, the recent report of GNAS mutations being detected in a significant proportion of parosteal osteosarcoma challenges the specificity of this mutation. As the number of cases reported in this study was small we set out to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…This prompted a follow‐up study of 97 osteosarcoma samples, 97 samples including 62 parosteal osteosarcomas and 24 low‐grade osteosarcomas which failed to reveal GNAS alterations. Our results supported the previous observations that GNAS mutations are highly specific for fibrous dysplasia and not detected in parosteal osteosarcoma …”
Section: Osteosarcomasupporting
confidence: 93%
See 1 more Smart Citation
“…This prompted a follow‐up study of 97 osteosarcoma samples, 97 samples including 62 parosteal osteosarcomas and 24 low‐grade osteosarcomas which failed to reveal GNAS alterations. Our results supported the previous observations that GNAS mutations are highly specific for fibrous dysplasia and not detected in parosteal osteosarcoma …”
Section: Osteosarcomasupporting
confidence: 93%
“…Our results supported the previous observations that GNAS mutations are highly specific for fibrous dysplasia and not detected in parosteal osteosarcoma. 15 Despite substantial research efforts, in the majority of cases the cause of osteosarcoma is not known (see below), and the diagnosis, subtyping, and grading remain defined by morphology alone. There are no recurrent genetic alterations or molecular profiles linking the prognosis of patients or their response to chemotherapy (other than the presence of MDM2 amplification, see above), and notably survival rates have not improved significantly over the last three decades.…”
Section: Fibrous Dysplasiamentioning
confidence: 99%
“…Recently, Sugiura et al also confirmed the presence of GNAS mutation in an osteosarcoma derived from FD in the hips. Other studies have previously demonstrated that GNAS mutations are not detected in conventional osteosarcomas . Combining these data suggest that a positive GNAS mutation status is highly diagnostic for FD and also for FD‐derived osteosarcoma.…”
Section: Discussionmentioning
confidence: 62%
“…While the incidence of MDM2 alterations were similar between the alveolar and embryonal RMS subtypes [15,16], TP53 mutations usually occurred in PAX fusion negative RMS but in generally less than 15% of those cohorts [17,18]. In OS, MDM2 amplifications could be detected in up to 83% of patient samples in individual reports and were more frequent in the parosteal subtype [19,20]. However, TP53 mutations were also prevalent in this histology, with 50e75% of patient tumour samples having at least one inactivating aberration [6,21].…”
Section: Resultsmentioning
confidence: 90%